Determination of β-Estradiol by Surface-Enhance Raman Spectroscopy (SERS) Using a Surface Imprinted Methacrylate Polymer on Nanoporous Biogenic Silica. (11th February 2022) - Mugo, Samuel M.; Lu, Weihao
Abstract: A phytoplankton derived nanoporous biogenic silica (BS) scaffold grafted with polymethacrylate β-estradiol molecularly imprinted polymers (MIP) film (MIP@BS) is reported as a selective platform for the determination of β-estradiol using surfaced-enhanced Raman scattering (SERS). The biogenic silica nanoparticles provided high surface area support for the MIP while serving as an active signal enhancement substrate for SERS. The MIP@BS platform demonstrated an excellent linear response (R 2 = 0.9996) between 0.1 and 4 ng/mL of β-estradiol standards. The limit of detection (LOD) for the MIP@BS SERS sensor for β-estradiol was 0.073 ng/mL. The MIP@BS SERS sensors were successfully evaluated for the determination of β-estradiol in milk, while demonstrating good stability and reusability.